Post-Mining Land Use Regulations and Practices in the United States of America: Lesson for Indonesia - Saputra, Rian; Hanum, Willy Naresta; Gunawan, Vincent Ariesto (CV. Ius et Ambientis, 2025)
This research assesses practices and legislation about post-mining land utilization in the United States. This paper examines insights from these practices and legislation within the Indonesian legal environment. This study employs a normative legal methodology within a comparative legal framework. The research indicates that the United States’s post-mining land use policies and practices are regulated by the Surface Mining Control and Reclamation Act (SMCRA) and different federal regulations supporting public purposes such as airports, shopping centers, and industrial zones. Rigorous supervision is enforced on post-mining land prior to its designation as appropriate for use. Specialized land management methods are implemented when mining occurs on prime agricultural land. The efficacy of reclamation is significantly contingent upon the use of scientifically substantiated optimal management practices that emphasize ecological restoration and biodiversity enhancement. Longitudinal studies in the United States about ecological reclamation demonstrate that effective strategies, including surface soil replacement and customized planting schemes, markedly enhance the likelihood of successful revegetation of former mining sites. The United States offers a robust framework underpinned by comprehensive policies and efficient implementation that Indonesia can adopt. Future adoption of post-mining land use policies and practices in Indonesia should establish a harmonious equilibrium that fosters sustainable development, preserves environmental integrity, and promotes active community engagement.